2016
DOI: 10.1159/000447458
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem/Stromal Cells in Regenerative Medicine: Can Preconditioning Strategies Improve Therapeutic Efficacy

Abstract: Mesenchymal stem/stromal cells (MSCs) are becoming increasingly important for the development of cell therapeutics in regenerative medicine. Featuring immunomodulatory potential as well as secreting a variety of trophic factors, MSCs showed remarkable therapeutic effects in numerous preclinical disease models. However, sustainable translation of MSC therapies to the clinic is hampered by heterogeneity of MSCs and non-standardized in vitro culture technologies. Moreover, potent MSC therapeutics require MSCs wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
127
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(130 citation statements)
references
References 120 publications
(161 reference statements)
2
127
0
1
Order By: Relevance
“…One promising therapeutic strategy is enhancing the release of a specific paracrine regenerative factor from stem cells by overexpressing it through genetic engineering (108). In agreement with this hypothesis, overexpression of VEGF in MSCs enhanced stem cell-mediated therapeutic efficacy in neural and cardiac repair (126), and intracerebral transplantation of BDNF gene-modified MSCs 1 day after middle cerebral artery occlusion promoted functional recovery and reduced infarct sizes in rats (127).…”
Section: Genetic Engineering Of Stem Cellsmentioning
confidence: 78%
See 1 more Smart Citation
“…One promising therapeutic strategy is enhancing the release of a specific paracrine regenerative factor from stem cells by overexpressing it through genetic engineering (108). In agreement with this hypothesis, overexpression of VEGF in MSCs enhanced stem cell-mediated therapeutic efficacy in neural and cardiac repair (126), and intracerebral transplantation of BDNF gene-modified MSCs 1 day after middle cerebral artery occlusion promoted functional recovery and reduced infarct sizes in rats (127).…”
Section: Genetic Engineering Of Stem Cellsmentioning
confidence: 78%
“…There is growing evidence that in vitro preconditioning of MSCs can optimize their paracrine potency and thus their therapeutic potential (82,(108)(109)(110). Preconditioning of MSCs includes exposure of in vitro MSCs to hypoxic or anoxic conditions (111-114); e.g., the addition of growth factors such as epidermal growth factor (115), glial cell-derived neurotrophic factor (116) (122), deferoxamine (123), or diazoxide (124).…”
Section: Preconditioning Of Stem Cellsmentioning
confidence: 99%
“…Although cultured MSCs have been shown to exhibit remarkable immunosuppressive capabilities, some studies have also pointed out that the immunoregulatory properties of MSCs may depend on culture conditions and on local microenvironment changes . If brain MPCs behave in a similar manner to MSCs, it may be suggested that MPCs in the brain of MS patients alter their phenotype and/or function in association with inflammatory activity.…”
Section: Discussionmentioning
confidence: 99%
“…Part 1 of the current special topic which was published in the preceding issue of Transfusion Medicine and Immunotherapy (issue 4, 2016) summarized the use of various stem cell populations such as mesenchymal as well as hematopoiesis- and adipose tissue-derived stem cells in the context of tissue regeneration, immune modulation and as transplantation additives [5,6,7]. In addition, several contributions provided comprehensive reviews on myocardial, cardiovascular and cardiovalvular tissue regeneration [8,9,10].…”
mentioning
confidence: 99%